PENGARUH STRATEGI DIGITAL MARKETING, DAN CUSTOMER EXPERIENCE TERHADAP LOYALITAS PELANGGAN DI KOPI SHEO - Halizahra, Rizka Irpat; Yogaswari, Tasya Patriot (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2025)
The intense competition in the coffee industry requires coffee shops to continuously innovate and build customer loyalty. Kopi SEO, as one of the local coffee shops, faces challenges in retaining its customers amid the proliferation of new coffee shops. This research aims to analyze the role of digital marketing strategies and customer experience in enhancing customer loyalty. By using a qualitative descriptive approach through interviews, observations, and SWOT analysis, this study identifies the internal and external factors that influence customer loyalty at Kopi SEO. The findings show that optimizing digital content, personalizing customer experiences, and having effective loyalty programs are crucial for regaining and growing market share. This research provides actionable recommendations to improve the sustainability and competitiveness of Kopi SEO.